Sustainable Futures: Exploring the Power of Mobile Technologies in Eco-Friendly Product Promotion - Naim, Arshi; Panda, Alaka; Sahoo, Smruti Rekha; Singh, Ritu; Hota, Sweta Leena (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Mobile technologies have expressively altered the way eco-friendly products are promoted, offering a dynamic and engaging platform for both businesses and consumers. These technologies propose green businesses and artisans with innovative ways to showcase environmentally aware products, such as organic food, sustainable fashion, and biodegradable goods, to a global audience that highlights sustainability. Through mobile apps, e-commerce platforms, and social media, organisations can involve directly with consumers, bypassing the traditional intermediaries, reducing costs, and fostering deeper connections. The structures, such as real-time product updates, communicating storytelling, user-generated content, and influencer partnerships, enhance consumer trust and build brand awareness. Moreover, the integration of mobile data analytics and personalised notifications allows businesses to effectively target niche markets, ensuring that eco-friendly goods reach the true consumers. On behalf of small-scale producers and Indigenous artisans, mobile technologies link the gap between rural craftsmanship and the demand in urban areas, opening doors to global markets. Though, challenges like digital literacy, infrastructure limitations, and increasing market competition must be addressed to ensure inclusive and equitable access for all stakeholders. This paper explores the transformative influence of interactive mobile technologies in promoting sustainable products, empowering green entrepreneurs, and advancing the global shift towards responsible consumption and eco-friendly lifestyles.